Síntese e caracterização de suportes porosos (scaffolds) à base de goma do cajueiro oxidada e carboxietil quitosana - Ferreira, Carlos Rhamon do Nascimento (2020)
Tissue engineering is an interdisciplinary field that aims to develop substituents that restore, maintain, or enhance the function of a deteriorated tissue. Cashew gum is composed of a major chain of galactose bound by C-1 and C-3, with branching of galactose bound by C-1 and C-6. This binding pattern makes this gum susceptible to oxidation by the periodate ion, resulting in a derivative with two aldehyde units per monosaccharide unit, and can act as a cross-linking agent against chitosan through the formation of Schiff base (C=N). This work proposes the synthesis of porous support (scaffolds) from oxidized cashew gum and carboxyethyl chitosan (CEQ) via Schiff base reaction forming crosslinked gels between the two polymers. The oxidized derivatives were characterized by FTIR and GPC. The modification was confirmed by the appearance of the band at 1735 cm-1in FTIR, which was attributed to the C=O bond. The introduction of the carboxyethyl group into the CEQ was also confirmed by the appearance of the band at 1771 cm-1, attributed to carboxylate C-O attachment. Hydrogels were prepared by mixing the GCOx with CEQ (both at 2% concentration) in the reason for 1:1 (v / v). From the gelation time it was observed that the hydrogels had Tgel values of less than 5 min. Rheological analysis showed that the amount of the aldehyde groups of GCOx plays an important role in the crosslinking process. The reaction between GCOx-CEQ is favored by increasing the temperature (20 °C to 60 °C) in the cross-linking process. The SEM showed that the hydrogels are formed by porous structures with pores of average diameters between 63±6 to 244±24 μm and with a porosity of 26,8±0,6 to 69,2 ±0,3%. Degradation studies in PBS showed that scaffolds show a slow mass loss over the 28- day period. The mechanical tests revealed a predominantly elastic behavior of the hydrogels. Thus it is possible to verify that the hydrogels present potential for application as porous supports in the regeneration of tissues, since they show good moldability of their properties.